Litter Production of The Mangrove Forest in The Tourism Area of Pariaman City - Nuke Leisya Ananta; Irma Leilani (Jurnal Serambi Biologi, 2022)
Litterfall is one of the important components that is taken into account in estimating primary productivity, especially to see its contribution to the estuarine ecosystem. The objective of the present study was to assess litterfall production rates of the Mangrove Forest in the Tourism Area of Pariaman City. Litterfall production in the study area was monitored from December 2021 - March 2022. The method used for litter collection is the litter-trap method. Sampling of mangrove litterfall were collected from 2 stations. Then, 6 litter-trap nets (Litter-trap) measuring 1x1 m2 were installed at each station which were randomly installed under the canopy of mangrove stands at a height of 1.5 m above ground level, so as to avoid the influence of tidal water. The litter production sample was then taken within 10 days for 6 times, the litter sample was then drying in air-circulation oven at 750C until constant weight was obtained. Then the litter mass was calculated within two months. The results of this study think that the average production in the Pariaman Mangrove Forest Tourism Park is 2.77 g/m2/day or 10.13 tons/ha/year with the order of the largest contributors being leaves > branches and twigs > generative organs.